2021
DOI: 10.2174/1386207323666201204141541
|View full text |Cite
|
Sign up to set email alerts
|

The Cosmetic Potential of The Medicinal Halophyte Tamarix Gallica L. (Tamaricaceae) Growing in The Eastern Part of Algeria: Photoprotective and Antioxidant Activities

Abstract: Aim and Objective: Currently, the use of ingredients from natural sources has gained great attention in cosmetic field especially for the development of new photoprotective formulations. Therefore, the present study aimed to evaluate the cosmetic potential of the methanolic crude extract and the ethyl acetate fraction of the medicinal halophyte Tamarix gallica (Tg) growing in the area of Tebessa in eastern of Algeria, by assessing their phenolic and flavonoid contents, photoprotective and antioxidant activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is related with a previous report that demonstrated the significant photoprotective effect of flavonoids in UV-B and UV-A range [1]. The protective factor of Ba-BuOH fraction (SPF=14.70±0.11) is higher than that of Ba-MeOH crude extract (8.20±0.22), indeed the higher SPF (290-320) value of Ba-BuOH is probably linked to its phenol and flavonoid contents, which is correlate well with several authors who demonstrated that the photoprotective effect is mainly associated with the levels of phenolics and flavonoids in plant extracts [33][34][35][36][37][38]. [23].…”
Section: Figure 4 Uv-absorbing Profile Of B Alpinumsupporting
confidence: 86%
“…This is related with a previous report that demonstrated the significant photoprotective effect of flavonoids in UV-B and UV-A range [1]. The protective factor of Ba-BuOH fraction (SPF=14.70±0.11) is higher than that of Ba-MeOH crude extract (8.20±0.22), indeed the higher SPF (290-320) value of Ba-BuOH is probably linked to its phenol and flavonoid contents, which is correlate well with several authors who demonstrated that the photoprotective effect is mainly associated with the levels of phenolics and flavonoids in plant extracts [33][34][35][36][37][38]. [23].…”
Section: Figure 4 Uv-absorbing Profile Of B Alpinumsupporting
confidence: 86%
“…The remarkable antioxidant activity observed in our study seems to be a feature of halophytes, although typically not as strong as the one displayed by PME. Studies have reported relatively low IC 50 values in the DPPH scavenging assay for extracts of halophytes, such as the species Tamarix gallica L. (aerial parts methanol extract, IC 50 = 14.05 ± 0.66 µg/mL) 33 , Limonium delicatulum (methanol extracts of leaves and roots, IC 50 = 10.58 ± 0.18 µg/mL and IC 50 = 5.79 ± 0.05 µg/mL, respectively) 34 , and Arthrocnemum indicum (Willd.) Moq.…”
Section: Resultsmentioning
confidence: 99%
“…On cell line, catalase and SOD activities also showed EthTg has the maximum antioxidant activity as compared to MthTg and AqTg. Recently, Lefahal et al 53 also revealed the antioxidant activity of methanol and ethyl acetate extracts of the Tamarix gallica in context of DPPH and TAC assay. Both extracts showed strong TAC (methanol = 287.01 ± 7.85, ethyl acetate = 246.7 ± 1.12 mg AAE/g) and DPPH (IC50 methanol = 14.05 ± 0.66, IC50 ethyl acetate = 27.58 ± 1.98 μg/mL) activity.…”
Section: Discussionmentioning
confidence: 99%
“…TFC also showed positive correlation with all antioxidant parameters (Table 3). Recently, Lefahal et al 53 demonstrated that antioxidant activity of Tamarix gallica extracts were possibly associated to polyphenols content and flavonoids. TPC and TFC correlation with antidiabetic activity indicated that if these contents were elevated, α-amylase ( R ² = 0.824 and R ² = 0.963 respectively) and α-glucosidase inhibitory activities ( R ² = 0.985 and R ² = 0.531, respectively) also be elevated.…”
Section: Discussionmentioning
confidence: 99%